Impact of wildfires on soil microbial nutrient functions in Karst forest ecosystems - Fu, Yuhong; Li, Xu; Li, Jianfeng; Liu, Xun; Zhang, Yanwei; Zhang, Yunlin (Frontiers in Microbiology, 2026)
This study investigates the impact of wildfires on the diversity and types of soil microbial functions within Karst forest ecosystems, and examines their relationship with soil nutrients. In particular, we focus on the Quercus fabri broadleaf and Pinus massoniana coniferous forests within areas affected by wildfires in Qiannan, located in the Karst area of Guizhou, Southwestern China. Analysis of soil microbial functional types associated with soil nutrients and their effects was performed using microbial amplicon sequencing technology. Significant differences in the functional diversity of soil bacteria and soil fungi associated with relevant soil nutrients were observed between the Q. fabri broadleaf and P. massoniana coniferous forests in the study area. After fire, the functional diversity of bacteria in both forest types increased significantly, resulting in a convergence in bacterial functional types. Fire enhanced the functional diversity of fungi in the P. massoniana forest; however, had no discernible effect on the Q. fabri forest. In addition, fire altered the types and abundance of microbial functions associated with soil nutrients, exerting a greater impact on bacterial functional types. The results also revealed that fire enhanced the abundance of TOC- and TP-related microbial functional types in both forest types, while reducing TK-related functional types. TN-related functional types increased in the Q. fabri forest but decreased in the P. massoniana forest. At the bacterial level, fire increased TOC-, TN-, and TP-related functional types in both forest types; however, reduced TK-related types. In fungal communities, fire increased TP-related functional groups in the Q. fabri forest while reducing TOC-, TN-, and TK-related groups. In contrast, in the P. massoniana forest, fire increased TOC- and TP-related groups but decreased TN- and TK-related groups. The research findings provide a scientific basis for the restoration and management of the post-fire forest ecosystems in Karst areas.